Characterization of the complete plastid genome of Psammosilene tunicoides (Caryophyllaceae), an endangered medical herb endemic to south-western China. Issue 2 (3rd July 2019) - Li, Yuling; Huang, Jiuxiang; Yao, Gang
Abstract: Psammosilene tunicoides is an endangered medical herb endemic to south-western China. In this study, the complete plastid genome of the species was characterized and assembled using the next-generation DNA sequencing method. The plastid genome is 153, 978 bp in length, including a large single copy (LSC) region of 83, 981 bp and a small single copy (SSC) region of 17, 489 bp, which were separated by a pair of inverted repeat (IR) regions of 26, 254 bp. The genome encoded 112 unique genes, including 78 protein-coding genes, four ribosomal RNA genes, and 30 transfer RNA genes. The overall GC content of the whole genome is 36.49%. The phylogenetic analysis based on 17 plastid genome of Caryophyllaceae revealed that P. tunicoides nested within the tribe Caryophylleae with strong support value.